2000
DOI: 10.4049/jimmunol.164.4.1705
|View full text |Cite
|
Sign up to set email alerts
|

Functional Maturation of Adult Mouse Resting Microglia into an APC Is Promoted by Granulocyte-Macrophage Colony-Stimulating Factor and Interaction with Th1 Cells

Abstract: A precise knowledge of the early events inducing maturation of resting microglia into a competent APC may help to understand the involvement of this cell type in the development of CNS immunopathology. To elucidate whether signals from preactivated T cells are sufficient to induce APC features in resting microglia, microglia from the adult BALB/c mouse CNS were cocultured with Th1 and Th2 lines from DO11.10 TCR transgenic mice to examine modulation of APC-related molecules and Ag-presenting capacity. Upon Ag-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
113
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 37 publications
15
113
0
Order By: Relevance
“…Our model is supported by several in vitro studies, including our own, indicating that coculture of encephalitogenic T cells with microglial cells in the absence of Ag resulted in an intermediate level of MHC class II expression and costimulatory molecule expression on microglial cells (intermediately activated microglial cells), while in the presence of Ag, the level of expression of these molecules reached a higher level (fully activated microglial cells) (10,33). Thus, presentation of self-Ag by preactivated CD45 high microglial cells to encephalitogenic T cells through MHC class II may facilitate the engagement of CD40-CD40L interactions and further perpetuate the activation of microglial cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our model is supported by several in vitro studies, including our own, indicating that coculture of encephalitogenic T cells with microglial cells in the absence of Ag resulted in an intermediate level of MHC class II expression and costimulatory molecule expression on microglial cells (intermediately activated microglial cells), while in the presence of Ag, the level of expression of these molecules reached a higher level (fully activated microglial cells) (10,33). Thus, presentation of self-Ag by preactivated CD45 high microglial cells to encephalitogenic T cells through MHC class II may facilitate the engagement of CD40-CD40L interactions and further perpetuate the activation of microglial cells.…”
Section: Discussionsupporting
confidence: 76%
“…The exact function of microglial cells is not known, but it has been suggested that microglial cells become activated and participate in propagation of inflammation in the CNS through Ag presentation and the production of proinflammatory cytokines/chemokines (5)(6)(7)(8). In vitro, the process of microglial cell activation has been characterized by the up-regulation of CD45, MHC class II, CD40, and CD86 (4,9,10), but this has not been studied extensively in vivo. One of the important molecules that is likely involved in microglial cell activation in vivo is CD40 (11), which is a member of the TNFR family and is a costimulatory molecule important for activation of B cells, macrophages, and dendritic cells (12).…”
mentioning
confidence: 99%
“…GM-CSF is also reported to enhance neonatal murine microglia APC functions (45). Therefore, human fetal microglia appear to retain some component of plasticity, possibly enhancing their stimulatory immune function when in the presence of T cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear cells (MNCs) from the CNS of MOG -immunized mice were isolated by Percoll gradient centrifugation by modification of published methods (12,13). Briefly, mice were sacrificed and transcardially perfused with ice-cold…”
Section: Isolation Of Cns Cells and Flow Cytometrymentioning
confidence: 99%